'Conjuring some magic': paganism and the musical and visual aesthetics of Florence + the Machine and Bat for Lashes. Issue 1 (3rd January 2019) - Smith, Erin Sweeney
Abstract: Magic and mystery shroud Florence + the Machine's and Bat for Lashes's performances and interviews, which frequently frame the two groups' frontwomen, Florence Welch and Natasha Khan, as 'witchy' or magical, or spur comparisons to Pagan aesthetics. This article investigates the unique ways the two bands use Pagan influences to speak to mainstream and Pagan audiences. Ultimately, the two groups set themselves apart from other bands through marketing that fuses commercialism with an esoteric religion. Florence + the Machine and Bat for Lashes create a 'Pagan chic' that draws in listeners through videos, instrumentation often featuring harp and tom-tom drums, fantasy-oriented lyrics, and stage props which use a Pagan lens to respond to current political events reminiscent of the counterculture of the 1960s and 1970s.